BASIC STUDENT LEADERSHIP TRAINING AND ISLAMIC GATHERING IN SHAPING THE LEADERSHIP CHARACTER OF GENERATION-Z IN SMK INFORMATIKA SERANG CITY - Murniasih, Eri; Wahyudin, Wawan; Hidayatullah, Hidayatullah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The purpose of this study is to find out how SMK Informatika Kota Serang forms leadership character in its students who are generation-Z. Leadership is the art of influencing and directing others to achieve common goals using principles such as obedience, trust, honour and cooperation. This leadership spirit is possessed by every generation, including Generation Z. The characteristics of this generation have a speciality that is close to technology because since birth they have known technology, growing up with the advancement of smartphones and social media. The research method used is descriptive qualitative method. Data collection was done through observation and literature study. Observations were made of the Basic Student Leadership Training and Islamic Gathering activities attended by students of SMK Informatika Kota Serang. Literature study was conducted by reviewing activity documents and literature on leadership. Based on the results of the study obtained information that the Basic Student Leadership Training (LDKS) and Islamic Gathering programme. LDKS and Islamic Gathering programmes have great potential to shape leadership character in Generation Z which is supported by strong exposure to technology. LDKS can bridge Generation Z in developing the ability to lead, communicate, cooperate, overcome challenges more effectively and increase motivation and self-confidence. And Islamic Gathering activities as a character application habituation programme can shape students to have good and effective leader characters.